Physico-chemical characteristics, cooking and texture of polished and brown rice of different varieties sold in Brazil (Research, Society and Development, 2020)
The diversity of whole rice grains with black and red pericarp has been valued in Brazil due to its different characteristics of color, texture, and also due to the association with health benefits. This work aimed to evaluate the physicochemical, cooking, and textural characteristics of different samples of polished and whole rice grains from different varieties marketed in Brazil. A total of 28 samples were collected and divided into 6 groups: polished white rice, white polished parboiled rice, whole white rice, whole red rice, whole black rice, and whole wild rice.  Moisture content, crude protein, ash, mineral content, hardness, and adhesiveness were analyzed. The cooking quality was evaluated through the determination of cooking time, swelling ratio, and volume expansion ratio. A strong correlation between the protein content and the hardness value of cooked grains was observed. The polished samples showed the lowest ash and mineral values and the shortest cooking time. A strong correlation was also observed for the volume expansion ratio and hardness of cooked samples. The data obtained contribute to a better understanding of the quality of the rice marketed in Brazil and demonstrate a large variation among samples in terms of physicochemical, cooking, and texture properties.